2021
DOI: 10.1159/000510831
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo with Progressive Repigmentation during Secukinumab Treatment in a Patient with Psoriatic Arthritis: A Case Report

Abstract: The proposed role of interleukin (IL)-17 in vitiligo pathogenesis, as well as the possible action of anti-IL-17A drugs on vitiligo, are not fully understood. The appearance of vitiligo as a paradoxical effect of treatment with anti-tumor necrosis factor-α drugs is an event well known in the literature, but is rarely described with anti-IL-17A drugs. In this case report, we describe a 42-year-old woman who developed new-onset vitiligo with repigmentation during successful secukinumab therapy for psoriatic arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, IL-17A inhibitor was rarely reported. Table 1 shows a summary of the published cases of IL-17 inhibitor-associated vitiligo in the literature ( 2 4 , 8 ). There has been primarily reported cases in association with secukinumab ( 2 , 4 ), one case with ixekizumab ( 3 ), and no case with brodalumab.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-17A inhibitor was rarely reported. Table 1 shows a summary of the published cases of IL-17 inhibitor-associated vitiligo in the literature ( 2 4 , 8 ). There has been primarily reported cases in association with secukinumab ( 2 , 4 ), one case with ixekizumab ( 3 ), and no case with brodalumab.…”
Section: Discussionmentioning
confidence: 99%
“…Giordano et al reported vitiligo with during secukinumab treatment in a psoriasis patient (Giordano et al, 2021). Goodwin et al reported the development of vitiligo patches over psoriasis lesions in a patient undergoing NB-UVB treatment for psoriasis (Goodwin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other biologics have also occasionally been associated with the development of vitiligo. Both cases of de novo vitiligo as repigmentation have been reported using IL‐17 inhibitors and IL‐12/23 inhibitors (Anthony et al, 2020; Giordano et al, 2021; Marasca et al, 2021; Speeckaert et al, 2019). A pilot trial using secukinumab did not find a stabilizing effect of IL‐17 inhibition in progressive vitiligo patients (Speeckaert et al, 2019).…”
Section: Clinical Entities Representing Different Aspects Of the Rela...mentioning
confidence: 99%